A mixed-methods evaluation of parent-assisted children’s friendship training to improve social skills and friendship quality in children with autism in Malaysia - Ong, Sing Yee; Roslan, Samsilah; Ahmad, Nor Aniza; Mohd Ayub, Ahmad Fauzi; Chen, Lee Ping; Zaremohzzabieh, Zeinab; Ahrari, Seyedali (Multidisciplinary Digital Publishing Institute, 2021)
Background: This study evaluates the effectiveness of parent-assisted children’s friendship training intervention for enhancing friendship quality and social skills among children with autism spectrum disorders (ASD). We conducted a quasi-experimental study to investigate the effective outcomes of social skills and friendship quality in the pre-and post-parent-assisted CFT intervention phases; Methods: to conduct a 12-week field session, 30 children with their parents were selected. The Social Skills Improvement System Rating Scales and the Quality of Play Questionnaire-Parent were used to assess the effectiveness of the parent-assisted children’s friendship training during pre-and post-intervention. A semi-structured interview with parents was conducted at the end of the session; Results: findings revealed that intervention improved the social skills of these children. Additionally, the friendship quality of children with ASD improved before and after the intervention, however, engagement remained unchanged. Parents also showed some sort of improvement after the session as they reported a heightened sense of fear and resistance, awareness, learning and adjustment, change is not easy, and identifying support; Conclusions: there was clear evidence that children with ASD benefitted from parent-assisted CFTs in terms of social skills and friendship quality. However, larger and controlled studies are required to draw firm conclusions about this kind of intervention.